The novel allele HLA‐B*35:564, identified by next‐generation sequencing in a Chinese individual. (31st December 2022) - Ma, Junxia; Liu, Keyao; Wang, Yan; Wang, Linlin
Abstract : The novel HLA‐B*35:564 allele differs from the HLA‐B*35:01:01:01 allele by one nucleotide in exon 3 at position 490.